Evaluation of International Patient Department Performance and its Effect on Medical Tourists Attraction among Hospitals Affiliated to Medical Sciences Universities in Tehran City - Sodabeh vatankhah; Ghasem Rajabi vasokolaei; sogand tourani; samira raoofi; susan rahimi (Tehran University of Medical Sciences, 2019)
Background:  Development of the tourism sector and health tourism specifically can improve the Non-Oil GDP. In this regard, in accordance with the policies of the Ministry of Health and Medical Education, international patient department establishment has been facilitatated health tourism development in the affiliated hospitals. This study aimed to evaluate the performance of international patient department  and its effect on the attraction of medical tourists among hospitals affiliated to Medical Sciences Universities in Tehran City. Matrials and Methods: This analytical cross-sectional study was designed and conducted in 2017. Study population consisted of all hospitals affilliated to  Tehran University of Medical Sciences (TUMS), Iran University of Medical Sciences (IUMS) and Shahid Beheshti University of Medical Sciences (SBMU). In this study,  hospital entrance criteria was certified by the Health Tourism Department of MOHME. Data was collected using the health tourism assessment checklist which approved by the MOHME. SPSS version 24 utilized to data analysis using descriptive and Inferential statistics. Results: The study results revealed that  the overall performance of international patient department was evaluated at a desirable level (87.5 score) in hospitals of Tehran city.  Hospitals had the highest rank of hoteling indices (95/100), in compliance with the regulations and functional indicators gained 87.03 and 82.2 score, respectively.  Also, data analysis highlighted that there was no significant difference between hospitals of TUMS, IUMS and SBMU. The establishment of international patient department had no effect on health tourists attraction. Conclusion: Considering the purpose and mission of international patient department to facilitate the provision of quality and satisfactory services in health tourists, management and oversight mechanisms for the standards implementation such as patient admission, follow up in the origin country and development of hospital marketing policies in order to attract international patients and increase hospital incomes are recommended.